SELECTION OF DIGITAL CAMERAS FOR PERFORMING AERIAL PHOTOGRAPHS USING UNMANNED AIRCRAFT - A.A. MIRZAEV; ?.A. URAKOV (International Journal of Innovations in Engineering Research and Technology, 2021)
The article describes the choice of unmanned aerial vehicles and digital cameras, one of the most widely used technologies in cartography. Since cartography is one specific area, there are clear objectives based on technical and regulatory documents. Aerial photography is one of the most effective methods for creating topographic maps, and it is worth discussing the features of calculating UAV image parameters. A method for determining the quality of cameras used for aerial photography from UAVs is described, and recommendations for the quality of aerial photography products are developed.